A Study of the γ-Radiolysis of N, N-Didodecyl-N′, N′-Dioctyldiglycolamide Using UHPLC-ESI-MS Analysis. Issue 5 (28th July 2016) - Roscioli-Johnson, Kristyn M.; Zarzana, Christopher A.; Groenewold, Gary S.; Mincher, Bruce J.; Wilden, Andreas; Schmidt, Holger; Modolo, Giuseppe; Santiago-Schübel, Beatrix
ABSTRACT: Solutions of N, N -didodecyl- N′, N′ -dioctyldiglycolamide in n -dodecane were subjected to γ-irradiation in the presence and absence of both an aqueous nitric acid phase and air sparging. The solutions were analyzed using ultra-high-performance liquid chromatography-electrospray ionization-mass spectrometry (UHPLC-ESI-MS) to determine the rates of radiolytic decay of the extractant as well as to identify radiolysis products. The DGA concentration decreased exponentially with increasing dose, and the measured degradation rate constants were uninfluenced by the presence or absence of acidic aqueous phase, or by air sparging. The identified radiolysis products suggest that the bonds most vulnerable to radiolytic attack are those in the diglycolamide center of these molecules and not in the side chains.